Feasibility study on microwave welding of thermoplastic using multiwalled carbon nanotubes as susceptor. (31st March 2021) - Foong, Phey Yee; Voon, Chun Hong; Lim, Bee Ying; Arshad, Mohd Khairuddin Md; Gopinath, Subash CB; Foo, Kai Loong; Rahim, Ruslinda A; Hashim, Uda
Despite manufacturers' goal of molding single component products from plastics, the structures of some of the products are far too complex to be molded as a single piece. Therefore, assembly of subcomponents into the final products is important for the manufacturing of many plastic-based products. To date, welding is the most efficient joining method for plastics. In this study, multiwalled carbon nanotubes were proposed as the susceptor for the microwave welding of high-density polyethylene considering multiwalled carbon nanotube is a good microwave absorber. multiwalled carbon nanotubes were first dispersed in ethanol in an ultrasonic bath to obtain a homogeneous dispersion. Multiwalled carbon nanotubes dispersion was dropped on the targeted area of the prepared dumbbell-shaped sample and dried in an oven at 45°C for 30 min. The sample was then subjected to 800 W microwave irradiation in the domestic microwave oven. The strength of the weld was tested by using tensile testing. Besides, the cross section of the welded joint was characterized by using scanning electron microscopy. The effect of microwave heating duration and the multiwalled carbon nanotube concentration in the dispersion were studied. It was found that the joint strength increased as the heating duration increase from 2 s to 8 s but decreased when the heating duration was further extended to 10 s. Scanning electron microscopic images showed that voids were formed at the joint interface when 10 s was used and resulted in the lowering of joint strength. In the study of the effect of the multiwalled carbon nanotube concentration in the dispersion, joint strength increased when the multiwalled carbon nanotubes concentration increased from 0.25 wt% to 0.75 wt%. However, the joint strength of sample with 1.00 wt% multiwalled carbon nanotube concentration decreased. The presence of a thick unwelded multiwalled carbon nanotubes layer at the joint interface for sample with 1.00 wt% multiwalled carbon nanotubes concentration as shown in scanning electron microscopic image was believed to cause the lowering of joint strength.